2017
DOI: 10.3390/ijerph14030319
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 Neutralizing Antibodies Seroepidemiological Research among Children in Guangzhou, China between 2014 and 2015: A Cross-Sectional Study

Abstract: A hand-foot-mouth disease outbreak occurred in 2014 around Guangdong. The purpose of this study was investigating the status and susceptibility of infectious neutralizing antibodies to enterovirus 71 among children so as to provide scientific evidence for the population immunity level of hand-foot-mouth disease and prepare for enterovirus 71 vaccination implementation. Serum specimens were collected from children in communities from January 2014 to March 2015 in Guangzhou. A total of 197 serum samples from chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…A systematic review has demonstrated that the antibody level against EV71 or CoxA16 dramatically increased among children aged 1-4 years [27]. Zhang et al believed that the immune level to enterovirus would accordingly increase with increasing age [28]. Our results also clarified that younger children have a greater likelihood of HFMD reinfection.…”
Section: Discussionsupporting
confidence: 63%
“…A systematic review has demonstrated that the antibody level against EV71 or CoxA16 dramatically increased among children aged 1-4 years [27]. Zhang et al believed that the immune level to enterovirus would accordingly increase with increasing age [28]. Our results also clarified that younger children have a greater likelihood of HFMD reinfection.…”
Section: Discussionsupporting
confidence: 63%
“…Seroprevalence rates of enterovirus A71 (EV‐A71) infection in different age groups worldwide . The data of 26 studies were collected according to their age groups and geographic locations and represented by a green‐yellow‐red colour heatmap.…”
Section: Ev‐a71 Infection Is Common: Evidence From Seroepidemiology Smentioning
confidence: 99%
“…The median age of infection (50% seroprevalence) was about 3 years in southern Vietnam, which is much lower than that in Singapore (>17 years) and Taiwan (>15 years) but is higher than that in Cambodia (1.5 years) and similar to China (3.1 years) ( Table 1) [17][18][19][20][21]. In another study collecting sera after the 2005 epidemic in HCMC, seroprevalences of EV-A71 antibody were 5.6% at 1 years of age and 12.2% at 2 years of age [22], which indicate that more young children under 3 years of age were infected in the 2011 epidemic (15.8% at 1 years of age; 23.5% at 2 years of age) than in the 2005 epidemic (S2 Table) [ [22][23][24][25]. In contrast, seroprevalences of EV-A71 antibody in Singapore and Taiwan were much lower in recent years [17,19,23,25].…”
Section: Resultsmentioning
confidence: 99%